A CONTRIBUIÇÃO DA FORMAÇÃO CONTINUADA PARA AS PROFESSORAS DE EDUCAÇÃO INFANTIL DO MUNICÍPIO DE SÃO PAULO - Sales, Cintia de Cássia Silva (2015)
This research addresses the ongoing education of Early Childhood Education teachers working in state schools belonging to the São Paulo Municipality network. The central question to be investigated is the contributions made by the proposal for ongoing education offered by the São Paulo City Board of Education to the referred teachers. The study was carried out based on the perception of the importance of ongoing education as a path and an exercise of self-reflection that enables the redefinition of the teacher s identity considering his/her historical construction process. This segment of education was chosen because several contemporary authors such as Beatrice Cerisara, Patricia Prado, Zeila Demartini, Júlia Formosinho and João Oliveira-Formosinho, among others, consider it an essential phase in which the dichotomy between care and education, as well as the identity of the teacher as an Educator, must be continually discussed. In this sense, this research first presents a theoretical discussion about Early Childhood Education teacher training in Brazil, concluding with a field research that evaluates the Strategic Action Project (PEA in Portuguese) as one of the proposals of ongoing training for Early Childhood Education teachers. The field research was carried out by means of semi-structured interviews with nine teachers from that municipal network. The research confirmed the relevance of PEA for the ongoing education of the teachers interviewed. The study also found that this project has been positively and significantly modified and improved with actions directed to the specific needs of Early Childhood Education, which conceive the child as a subject of right, who has a voice and many competences. The research also observed how PEA contributes to the ongoing education when, in collective moments, it allows peer exchange and the consequent reflection about their practices, helping teachers to became more autonomous, aware of their important role as mediators of the child learning construction process.